Associations between levels of physical activity and satisfaction with life among Norwegian adolescents: a cross-sectional study - Grasaas, Erik; Ostojic, Sergej; Sandbakk, Øyvind (Frontiers in Sports and Active Living, 2024)
Background: A robust association between physical activity (PA) and satisfaction with life (SWL) has been established, wherein self-efficacy has been identified as a mediator across different populations. However, there is a need to further examine the relationship between PA and SWL and whether self-efficacy act a as mediator within different levels of PA among Norwegian adolescents. Thus, the objective of this study was to explore the relationship between levels of PA and SWL by testing for self-efficacy as a possible mediator.Methods: Cross-sectional data from the 2022 Norwegian Ungdata Survey was utilized. Data included demographics and various health data that was collected anonymously. The electronic survey took place in classrooms and was administered by the respective teacher. Permission to access and use data was approved by the Norwegian Agency for Shared Services in Education and Research (SIKT). Statistical analyses were conducted using the PROCESS macro by Andrew Hayes for SPSS software.Results: Descriptive findings revealed that girls reported lower self-efficacy than boys (14.2 vs. 15.5, with a maximum of 20) and lower SWL (6.8 vs. 7.6, with a maximum of 10). About one out of five girls and one out of seven boys reported no days of weekly PA, whereas 4% of girls and 9.5 % of boys adhered to the PA-recommendation of 60 minutes of daily exercise. Associations between PA levels and SWL was mediated by self-efficacy (all p<0.05), with the highest indirect effect (56.3%) revealed in the association between those adhering to the PA-recommendations and SWL.Conclusions: Norwegian girls reported more sedentary behavior, less PA, lower self-efficacy, and lower SWL than boys across all grade levels. Mediation analysis revealed that up to 56.3% of the enhancement in SWL among those adhering to 60 minutes of PA recommendations was explained by increased self-efficacy. Norwegian government and policymakers should promote initiatives and regulations focusing on higher levels of PA to foster a resilient adolescent population with higher individual beliefs and higher subjective wellbeing.